PENERAPAN ASAS PROPORSIONALITAS DALAM PELAKSANAAN KERJASAMA PENGGADUHAN TERNAK SAPI ANTARA PEMERINTAH DENGAN KELOMPOK TANI KOPERASI UNIT DESA SIDO MULYO DI KABUPATEN TANJUNG JABUNG BARAT - Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Patterns of livestock business partnership among farmers / ranchers are often known as "rowdy". This livestock rowdy system is also used by the government in efforts to develop livestock in the community and increase the welfare of farmers / ranchers. The farmer group who are members of Sido Mulyo Cooperative in Dusun Mudo Village Muara Kapalik Sub-district of Tanjung Jabung Barat Regency is one of the farmer groups that get cattle donation from the government with the rowdy system tied up with the Letter of Agreement. An agreement with the pattern of partnership should apply the principle of proportionality in order to balance the rights and obligations of the parties in accordance with their respective capabilities.Keywords : Partnership Patterns, Rowdy, The Principle Of Proportionality.